1987
DOI: 10.1007/bf00316205
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum hydrocarbon toxicity in vitro: effect of n-alkanes, benzene and toluene on pulmonary alveolar macrophages and lysosomal enzymes of the lung

Abstract: The in vitro effects of straight chain alkanes (nC6-nC10), benzene and toluene on pulmonary alveolar macrophages (PAM) of rats and rabbits was studied. The concentrations used ranged from 0.02 to 1.0 mM. All hydrocarbons used in the study were cytotoxic to isolated cultured PAM cells in a dose-dependent manner. The LC50 for these hydrocarbons towards rat PAM cells was estimated to be 1.0 mM for nC8, 2 mM for nC7, 5 mM for nC9 and 10 mM for nC6, nC10, benzene and toluene. Rabbit PAM cells were more sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…Previous studies have indicated that exposure of rat and rabbit pulmonary alveolar macrophages to toluene, in vitro, induced lipid peroxidation (Suleiman, 1987). These results parallel our findings of toluene-induced increases in TBARS in the liver.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have indicated that exposure of rat and rabbit pulmonary alveolar macrophages to toluene, in vitro, induced lipid peroxidation (Suleiman, 1987). These results parallel our findings of toluene-induced increases in TBARS in the liver.…”
Section: Discussionsupporting
confidence: 92%
“…However, in humans and in animals, small quantities of toluene may be converted by phenolic compounds by the enzyme arylmonooxygenase and by epoxide formation of the aromatic nucleus, leading to potentially harmful reactive intermediates (Gerarde and Ahlstrom, 1966;Bakke and Scheline, 1970;Laham, 1970;Jerina and Daly, 1974). In vitro studies of benzene and toluene in pulmonary alveolar macrophages have shown a loss of cell respiration and a dose-dependent and time-dependent increase in lipid peroxidation (Suleiman, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Toluene has been shown to induce lipoperoxidation in pulmonary alveolar macrophages [20], while p-xylene, a structural analogue, caused similar increases in lung microsomes [21]. Given these findings, this study was undertaken to determine whether reactive oxygen species and related membrane events play a role in the neurotoxicity that results from toluene exposure.…”
mentioning
confidence: 99%
“…Most of the articles dealing with the activities of lysosomal enzymes in AM after in vivo or in vitro exposure to respirable substances describe the intra -and extracellular concentration or activity of these enzymes after incubation of the isolated AM in the medium. Increased (often dose dependent) leakage into the medium (and consequently decreased activities in the intracellular space) are mentioned 20,[26][27][28] . We did not incubate the isolated BAL cells because we did not want to monitor the leakage of lysosomal enzymes.…”
Section: Figmentioning
confidence: 99%